Can your SOA make you money? reuse of services + agility = ROI. - Linthicum, David
Why do we do what we do? I mean, why do we design and implement SOAs? The truth is we do so to improve our business, thereby making it more adaptable and ready to accept change without major disruptions. However, what does this mean to the bottom line?